Putting essential understanding of functions into practice : in grades 9 - 12 - Ronau, Robert N., ....-; Meyer, Dan, ....-; Crites, Terry, ....-; Dougherty, Barbara J., ....- (National Council of Teachers of Mathematics : Reston, 2014)
Do your students think that the vertical line test is indispensable and foolproof for determining whether a relationship is a function? Do they believe that every function can be modeled by an equation? Do they interpret the graph of a function as the function itself? What tasks can you offer—what questions can you ask—to determine what they know or don't know—and move them forward in their thinking? This book focuses on the specialized pedagogical content knowledge that you need to teach functions effectively in grades 9–12. The authors demonstrate how to use this multifaceted knowledge to address the big ideas and essential understandings that students must develop for success with functions—not only in their current work, but also in higher-level mathematics and a myriad of real-world contexts. Explore rich, research-based strategies and tasks that show how students are reasoning about and making sense of functions. Use the opportunities that these and similar tasks provide to build on their understanding while identifying and correcting misunderstandings that may be keeping them from taking the next steps in learning.
Keywords: Functies (wiskunde).